Transfer of information using surface-plasmon-polariton waves - Agrahari R.; Lakhtakia A.; Jain P.K. (My University, 2025)
The limitations of electronic and optical interconnects inside a semiconductor chip could be overcome by the used of plasmonic-polaritonic interconnects whereby information is carried by surface-plasmon-polariton (SPP) waves guided by planar metal/dielectric interface. Investigating the propagation of a pulse-modulated carrier SPP wave when the metal is either abruptly terminated or bent and the dielectric material is air, we have found that SPP-wave-based interconnects can be effective conduits of information. © COPYRIGHT SPIE. Downloading of the abstract is permitted for personal use only.